Effects of exogenous applications of gibberellic acid on the development and quality of jabuticaba fruits (2020)
The jabuticaba is a native species that is seeing increased industrial exploitation because of its organoleptic and functional characteristics, making it attractive for food and pharmaceutical products. However, the fruit composition is not favorable for processing because of the abundance of seeds. Techniques already established for other crops should be studied to improve industrial use characteristics. Thus, the objective of this study was to evaluate the development and organoleptic quality of jaboticaba fruits as a function of exogenous applications of gibberellic acid on the stem of plants in three reproductive stages. The treatments consisted of four concentrations of gibberellic acid (0, 50, 100 and 200 mg L-1) applied to jabuticaba plant stems in three reproductive phenological stages (flower buds, anthesis and post-flowering). A randomized complete block design was used with a factorial scheme (4×3) with six replications. It was observed that applications during anthesis and after flowering resulted in lower seed mass values and seed numbers and higher pulp yield, on average 23.08, 22.97 and 20.87%, respectively. The treatment with flower buds and increased gibberellic acid concentrations also resulted in an increased pulp yield, up to a maximum of 12.58%. Thus, it was concluded that the application of increasing concentrations of gibberellic acid, up to 200 mg L-1, improves pulp yield without altering the organoleptic characteristics of jabuticaba fruits and that applications at post-flowering or anthesis provide higher quality for industrial uses.